Pengaruh Metode Storytelling Terhadap Pemahaman Cerita Rakyat Pada Mata Pelajaran Bahasa Jawa Siswa Kelas V SD Negeri 1 Pecangaan Wetan - Eka Nor Shoviana; Dwiana Asih Wiranti (CENDEKIA PENDIDIKAN, 2026)
Folklore learning in Javanese language subjects plays an important role in preserving local culture while instilling character values in students. However, “students’’ understanding of folklore still needs improvement because learning activities tend to be teacher-centered and provide limited opportunities for active student participation. This study aimed to determine the effect of the storytelling method on students’ understanding of folklore in Javanese language learning among fifth-grade students at SD Negeri 1 Pecangaan Wetan. The study employed a quantitative approach using an experimental method with a One Group Pretest-Posttest Design. The sample consisted of 33 students selected through a total sampling technique. Data were collected using validated and reliable pretest and posttest instruments. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, and the Paired Sample T-Test. The results showed that the mean pretest score of 73.1 increased to 91.7 in the posttest. The normality test indicated that the data were normally distributed, with significance values of 0.406 for the pretest and 0.379 for the posttest. The Paired Sample T-Test revealed a significance value of p < 0.001, indicating that the null hypothesis was rejected and the alternative hypothesis was accepted. Therefore, the storytelling method has a significant effect on ‘‘students” understanding of folklore and can be used as an effective alternative teaching method in Javanese language learning at the elementary school level.